Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan dan Loyalitas Pelanggan (Studi pada Pasien Rawat Inap di Rumah Sakit NU Tuban) - As'ad, Achmad Shofiyyuddin; Noermijati (Jurnal Aplikasi Manajemen, 2013)
This study aims to analyze the impact of service quality and price on customer satisfaction and customer loyalty, as well as the influence of customer satisfaction on customer loyalty in hospital inpatients NU Tuban. Technical analysis of the data in this study using the Partial Least Square ( PLS ).The results showed that the quality of service and price positive and significant impact on customer satisfaction, as well as indirect effect on customer loyalty through customer satisfaction. Customer satisfaction is positive and significant effect on customer loyalty.